THE INFLUENCE OF FINANCIAL PERFORMANCE ON COMPANY’S IPO PRICE - Rani Wulandari Lestari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research explains about the effect of financial ratios (Net Profit Margin (NPM), Return on Assets (ROA) and Return on Equity (ROE)) on company IPO price Sampling method used is the census method that generates the sample of 36 companies that conduct Initial public Offering (IPO) on Indonesian Stock Exchange (IDX) in the period 2009-2011. Partially, the results of this study explains that the independent variables have a significant influence on IPO’s pricing are NPM, ROI and but simultaneously, the three independent variables have a significant influence om initial stock price. The high NPM, ROI and ROE showed that the company's financial performance runs very well, which can increase the interest of investors and the price of IPO when the company is going to do goes public. Key Word: IPO’s price, NPM, ROI, ROI